Mycotoxigenic fungi and ochratoxin contamination in greek grapes and wine - Natskoulis, Pantelis (Cranfield University, 2009)
Basic concept of the present study was to examine ochratoxin A (OTA) presence in Greek grapes on the field, during winemaking and at the final product, wine. Finally the project was an attempt to integrate approaches for controlling the responsible fungus (Aspergillus carbonarius) in Greece, together with ways to eliminate presence of OTA in wine. To this end the effect of water activity (aw), and other important environmental factors such as temperature, pH and strains and their interactions on growth/OTA production were studied. Greek A. carbonarius isolates grew optimally at 30-35ºC and 0.96 aw, while maximum OTA production occurred under suboptimal growth conditions (15-20ºC & 0.93-0.96 aw). Greek isolates examined in the present study were more xerotolerant than others of the Mediterranean basin. Studies were performed in organic and non-organic vine grape production systems in an attempt to correlate the presence of total Aspergillus section Nigri and ochratoxigenic A. carbonarius strains with meteorological conditions and geographical localization. Besides the studies on ecophysiology and in the field, growth data were fitted to several predictive models in order to contribute to the evaluation of solutions that can be practically used in Greece for protecting production from OTA contamination. The effect of temperature and aw on the growth of A. carbonarius strains could be satisfactorily predicted under the experimental conditions studied, and the proposed boundary models for growth/no growth and toxin/no toxin production could serve as a useful tool. Another component of the present thesis was the investigation of OTA content in Greek wines and the correlation of the results with the origin of production, the year of production, the colour and type, and other vinification techniques. This showed that Greek red, rosé and white wines had lower levels and incidences of contamination than wines from other countries of the Mediterranean basin. Moreover, Greek wines were below the European limit of 2.0 μg L-1. Although contamination with the mycotoxigenic fungus was rather high, most of the samples contained low levels of OTA. The key areas of concern were the results from the southern regions of Greece, mainly Peloponnese and Aegean Islands, especially for the dessert type ones. In order to understand the partitioning of OTA during vinification and clarification processes in Greek wines, an experimental vinification process was performed using different fermentation techniques (presence or absence of artificially inoculated OTA, A. carbonarius, starter yeasts). The general trend for the evolution of OTA concentration throughout the vinification process was a decrease of the initial concentration which was more significant in the first days of fermentation when acceleration of yeast population took place. This data has been integrated to produce a prevention management strategy in Greece to minimise OTA contamination in the grape-wine chain.